A One-pot Multicomponent Synthesis of Naphthoxazin-3-one Derivatives Using Amberlite IRA-400 Cl Resin as Green Catalyst - Harichandran, Gurusamy; Parameswari, Parkunan; Shanmugam, Ponnusamy (Letters in Organic Chemistry, 2018)
An efficient Amberlite IRA-400 Cl resin catalyzed, solvent-free, one-pot synthesis of 1- aryl-1,2-dihydro-3H-naphtho[1,2-e][1,3]oxazin-3-ones via three-component reaction of arylaldehydes, urea, and β-naphthol are described. This method offers advantages such as easy work-up, low environmental impact, shortened reaction times, and high yields. The catalyst recovered was reused four times without significant loss of catalytic activity.
Keywords: three-component reaction